How digital leadership impacts community resilience: a moderated mediation model - Guanhu Zhao; Guanhu Zhao; Fazhen Zhao; Fazhen Zhao; Fazhen Zhao; Xu Hui; Xu Hui; Yanan Wu; Yanan Wu; Xuemei Zhao (Frontiers in Public Health)
IntroductionCommunity resilience is crucial for communities to effectively respond to disasters such as public health emergencies. Digital technology and leadership are integral to building community resilience; however, the impact of digital leadership on community resilience has been underexplored.MethodsThis study administered a questionnaire survey to 306 participants to examine the impact of digital leadership on community resilience. Furthermore, it also explored the mediating role of knowledge sharing and the moderating role of community trust.ResultsWe find that (1) digital leadership, knowledge sharing, community trust and community resilience are positively correlated with each other; (2) knowledge sharing partially mediates the relationship between digital leadership and community resilience; and (3) community trust moderates the effect of digital leadership on knowledge sharing. Specifically, under the condition of high community trust, digital leadership is more effective in predicting community resilience.DiscussionThe findings of this study not only contribute to the existing literature on the antecedents of community resilience but also elucidate the influence mechanism of digital leadership on community resilience from a micro perspective. Furthermore, this study provides practical recommendations for enhancing community resilience in the digital era.